INVESIGATING THE LISTENING NEEDS OF THE TENTH RADE STUDENTS ON MAN KEMANTAN DARAT KERINCI - Yoki Irawan (Universitas Negeri Padang, 2017)
This study mainly aimed to investigate the needs in learning English and to gather the information about problems faced by the tenth grade students’ of MAN Kemantan Darat Kerinci related to listening material. In order to achieve these objectives, a small scale need analysis wascarried out in advance. It was carried out through survey study that involved77 tenth grade students and 4 English teachers of MAN Kemantan Darat Kerinci. The data were collected through a questionnaire to find out the data about students’ needs, interview guidance for collect the data about teachers’ needs and documentation to find out the curriculum demand. The data were analyzed through descriptive quantitative. Based on the data analysis,the resultsshowed that 1) The syllabus was relevant tothe students’ needs but the material, generally, were not relevant to the students’needs. 2) There were still many students have difficulties in mastering listening skills in learning English in terms of input, topic, language, and task.3) The students were need to exposure to material that delivered in various ways (multimedia) in order to improve their accuracy and attention in learning listening skill. Based on the result of research discussion, it was suggested to applied multimedia-based in developing listening material for tenth grade students of MAN Kemantan Darat.